THE LOWER REACHES OF THE VOLGA AND THE NORTHERN CASPIAN AT THE CROSSROADS: TIME AND PEOPLE, PAST AND PRESENT - VIKTORIN, Viktor (CENTRAL ASIA AND THE CAUCASUS, 2004)
From time immemorial migrations, ethnic migrations included (that were sometimes artificially encouraged or just as artificially restrained) have created and continue to create problems for old-timers and newcomers alike; by the same token the academic community was forced to conceptualize this rather complicated phenomenon. At the same time,the great migrations of people” have left their in-delible traces in world history. They are a vehicle of cultural exchange, a powerful stimulus of ethnogenesis and ethnic contacts that shaped and changed ethnic make-ups of limited and vast territories. Sociologists have already pointed out that the turn of the 21st century is marked by landslide migrations all over the world. People move for natural reasons or are forced or provoked to migrate.Forced migrations were caused by the tragic end of the Soviet Union and the crisis of the Russian Federation’s administrative structure. They reached their peak in the 1990s when huge masses of people moved to new places or returned to old homes long abandoned by their ancestors. (Exodus is prob-ably an apt term to be used in this context.) Sometimes natural and forced migrations coincide in time and place; in such cases their ethnic descriptions may become even more obvious or may complement the main features of such movements.here are points of attraction and points of transit migrations normally found along borders of neigh-boring states or along administrative borders inside a country. The present situation is of critical importance for Russia; when dealing with the most urgent is-sues we should demonstrate well-balanced, bold and novel approaches.1 The way these issues are treated in the Astrakhan Region has already attract-ed academic attention and invited several opinions about the processes and possible approaches.2